Schottky and Poole-Frenkel conduction mechanisms in ZrON/SiC system / Vanessa Lusus - Vanessa, Lusus (2020)
In this work, the conduction mechanisms of Schottky Emission (SE) and Poole–Frenkel (PF) Emission for the ZrON/SiC system with a temperature range between 400 oC to 900 oC were analyzed. Understanding of the conduction charge mechanisms will help to estimate leakage characteristics of the ZrON/SiC system. Based on the J-E plot measured at different temperatures for 15 minutes, the obtained r2 was ranged between 0.90–0.98, which confirmed the data obtained complied with the standard SE model. Furthermore, the data plotted from the Effective Barrier Height Extracted from the SE plot showed the highest values of